Hydrological impact of climate change in the Jaguari river basin at Cantareira reservoirs system - Domingues, Leonardo Moreno (2020)
A recent unprecedented drought at the Cantareira reservoirs system with spread water shortage affected much of São Paulo city during 2014 and 2015. Climate projections to this area indicate high concordance that it will be warmer in the late 21st century, but changes in rainfall are mixed among models. Due to its key importance in supplying water to a densely populated region, understanding the potential changes in the regional water budget of such a system under climate change is strategic. With a thoroughly calibrated physically-based SWAT model, we used forcing-response relationships of key climate variables (temperature, rainfall, humidity and CO2 concentration) based on CMIP5 projections under RCP 8.5 scenario, to estimate the impact of climate change in the surface water budget over the Jaguari river basin, the main supplier of Cantareira reservoirs system. This approach aimed to circumvent common issues of regional impact assessment with hydrological modeling as the use of few global models and the choice of the downscaling method. With temperature increase spanning from 1 to 5°C, we found opposite responses in the future due to rainfall uncertainty in the projections: under increased rainfall, the mean evapotranspiration (discharge) is about to increase up to 25% (90%); under less precipitation, evapotranspiration decreased up to about 10% and discharge to 50%. Besides, we showed that the higher CO2 concentration had a strong effect on depleting the stomatal conductance in the future, resulting in a reduced evapotranspiration, which in turn, increased the discharge in near proportion. Temperature and relative humidity alone played minor roles when compared to the rainfall and CO2 concentration. With respect to the responses of extreme events, we showed that maximum discharge can reach more than twice the historical levels in the future with increasing rainfall and minimum ow can reduce up to about 30% in case of less precipitation. These two directions seem well likely so far, and caution to overcome the bad effects of either are needed for investigation and planning in more detail.